UAE Resident Users’ Perceptions of Healthcare Applications from Dubai Health Authority: Preliminary Insights - Shamsa AlSuwaidi; Immanuel Azaad Moonesar (Dubai Medical Journal)
Background: Innovations in healthcare are a way to sustain and improve health outcomes, usually done in a cost-effective way. Thus, the Dubai Health Authority (DHA) is keen on launching the best innovations in all areas such as health apps, telecommunications, electronic patient health records, and others. Objectives: DHA apps users within the United Arab Emirates (UAE) were studied to determine the extent they were satisfied with the available medical health apps; there are limited studies on users’ perceptions on health innovations in the UAE. Method and Results: The quantitative methodology included data collection from a sample of 396 apps users. The technology acceptance model (TAM) provided an appropriate framework for this research, independent variables included gender, nationality, education, and age, and the dependent variables included the users’ perceptions related to usefulness, ease of use, and usability as well as satisfaction. The results of the study revealed a statistically significant difference based on the abovementioned independent variables. Conclusion: The research adds value for policymakers when considering and evaluating the current health apps available in the DHA; the research findings could positively influence public policies for the development of health innovations across the UAE region. Future research should aim to include other factors that may have an influence on the adoption of technology and uncover further reasons that motivate or discourage users.